An assessment of the likely impact of strain-related phenotypic plasticity on hominin fossil species identification - Collard, M.; Lycett, S.J. (South African Journal of Science, 2010)
It has been proposed that strain-related phenotypic plasticity may be a major confounding factor in attributing hominin fossils to species. The study reported here tested this hypothesis with craniometric data from the great apes and Colobus guereza. We divided the measurements into three groups: measurements of features subject to high masticatory strain, measurements of features subject to low-to-moderate masticatory strain, and measurements of features that do not remodel and therefore are not prone to strain-related phenotypic plasticity. Next, we used the coefficient of variation and ANOVA to investigate whether masticatory strain is a cause of variability. These analyses partially supported the hypothesis. The predicted differences between the high-strain measurements and the other measurements were found in the majority of the species. However, the coefficient of variation values for the low-to-moderate strain and non-phenotypically plastic measurements were indistinguishable. Thereafter, we used discriminant function analysis to compare the ability of the three groups of measurements to assign specimens to species. This analysis did not support the hypothesis. The high-strain measurements were less effective than the other measurements, but the low-to-moderate strain measurements were more effective than the non-phenotypically plastic measurements. In addition, better discrimination was achieved when all the measurements were employed than when just the non-phenotypically plastic measurements were utilised. We conclude from this that strain-related phenotypic plasticity is unlikely to impede hominin alpha taxonomic research.